The big wild soul of Terrence Cole : an eclectic collection to honor Alaska's public historian - Soos, Frank; Ehrlander, Mary F.; Cole, Terrence, 1953- (Fairbanks, AK : University of Alaska Press, 2019)
"This book is an eclectic festschrift dedicated to Alaska historian and writer Terrence Cole."--Provided by publisher.
Front Matter -- Contents -- I got off the Bus -- Terrence Cole as Researcher and Writer -- The Inimitable Professor Terrence Cole -- I Have Known Terrence Cole -- Arctic Terror -- "Dogs is Dogs" -- Don't You Know This Place Will Kill You? -- Joseph Hazelwood and the One Thousand Dozen -- Sydney Laurence, Belle Simpson, and the Nugget Shop -- Too Good to be True -- "No Dogs or Natives Allowed" -- Contingency and Alaska History -- Boom, Bust, and Build -- Between Two Empires -- The Hunter & The Copper-Eyed Bug from Mars -- Site Summit -- The <NN> Cannery History Project -- Roads Versus Runways -- The Mysterious Process of Historical Research -- Index
"Contributors include: Dermot Cole, Gerald McBeath, Mary F. Ehrlander, Ronald K. Inouye, Carolyn Kozak Loeffler, Sherry Simpson, Frank Soos, John Straley, Kes Woodward, Chris Allan, Ross Coen, Stephen Haycox, Lee Huskey, David Eric Jessup, Dan O'Neill, Leighton M. Quarles, Katherine Ringsmuth, Dirk Tordoff, Russ Vanderlugt and Heath Twichell."
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Cole, Terrence, -- 1953-; Cole, Terrence, -- 1953-; Cole, Terrence, -- 1953-; Alaska -- Civilization; Alaska -- History; Historians -- Alaska -- Biography; Alaska -- Civilisation; Alaska -- Histoire; HISTORY / United States / State & Local / General; Civilization; Historians; Alaska; Biographies; History